The Transformational Mission: Using the Departmental Mission to Initiate Meaningful Change - Craig D Hlavac (Academic Chairpersons Conference Proceedings, 2015)
This session will provide participants with an overview of the elements of exemplar mission statements, followed by the presentation of several practical methods for using the departmental mission to initiate and sustain meaningful change. Participants will examine and discuss common elements of missions from business, non-profits, and higher education, and will use this information to inform discussion surrounding their own departmental missions. The session will also allow participants to dialogue in small groups about positives and negatives of their own department’s mission statements, providing an opportunity for feedback and potential revisions.
Keywords: Leadership; Mission Statements; Mission-Based Management; Change